2020
DOI: 10.1111/hepr.13548
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and prognosis of hepatocellular carcinoma in the Guangdong liver cancer cohort study

Abstract: Adherence to dietary recommendations has been linked to a reduced risk of developing hepatocellular carcinoma (HCC) and dying of chronic liver disease. However, its role in the prognosis of HCC is still unclear. We prospectively investigated the association of two dietary quality indices, the Chinese Healthy Eating Index (CHEI) and the Healthy Eating Index 2015 (HEI 2015), with all cause and HCC specific mortality in a large prospective cohort of HCC survivors. Methods: We included 887 patients with newly diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…By comparing the CHEI of 720 liver cancer patients and healthy individuals, Chen et al discovered that the probability of primary liver cancer dropped by 57% (OR = 0.43, 95% CI: 0.38–0.50) with each five-point rise in score [ 41 ]. Luo et al also found that in the Guangdong Cohort Study, 887 patients with liver cancer were followed for 797 days, and higher CHEI scores were substantially linked with mortality from all causes (hazard ratio (HR) = 0.75, 95% CI: 0.58–0.98) and mortality from liver cancer (HR = 0.74, 95% CI: 0.56–0.98) [ 42 ]. In addition, Maitiniyazi’s study also found that adhering to Chinese dietary guidelines can help relieve mental symptoms and discomfort in breast cancer patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the CHEI of 720 liver cancer patients and healthy individuals, Chen et al discovered that the probability of primary liver cancer dropped by 57% (OR = 0.43, 95% CI: 0.38–0.50) with each five-point rise in score [ 41 ]. Luo et al also found that in the Guangdong Cohort Study, 887 patients with liver cancer were followed for 797 days, and higher CHEI scores were substantially linked with mortality from all causes (hazard ratio (HR) = 0.75, 95% CI: 0.58–0.98) and mortality from liver cancer (HR = 0.74, 95% CI: 0.56–0.98) [ 42 ]. In addition, Maitiniyazi’s study also found that adhering to Chinese dietary guidelines can help relieve mental symptoms and discomfort in breast cancer patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Lan et al [ 89 ] that enrolled 782 patients with primary liver cancer and evaluated their habitual dietary intake found that an urban prudent dietary pattern (consisting of higher intake of eggs, mushrooms, dairy products, soy foods and nuts, and lower intake of refined grains) and a traditional Cantonese dietary pattern (characterized by a high intake of fruit and vegetables, Cantonese soup, fish, and Chinese herb tea) have been associated with a lower risk of primary liver cancer (OR: 0.25 and 0.61, respectively), while a diet rich in meat and preserved foods increased the risk (OR: 1.98). Moreover, a prospective study that enrolled 887 patients with newly diagnosed HCC suggested that a higher adherence to the 2016 Chinese Dietary Guidelines was associated with a lower risk of HCC-specific mortality (HR: 0.74) and all-cause mortality (HR: 0.75)[ 90 ].…”
Section: Interventions To Prevent Nafld/nash-associated Hccmentioning
confidence: 99%
“…Thus, most of the clinical recommendations focus on dietary patterns rather than specific dietary components. Evidence supporting the relationship between specific dietary patterns and HCC is limited to large observational prospective cohort studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and subsequent meta-analyses [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Such approaches limit the ability to parse out the combined impacts of obesity, smoking, and alcohol intake and increasing physical activity and plant-centered dietary patterns.…”
Section: Treatment Strategies For Obesity and Their Association With ...mentioning
confidence: 99%